2003
DOI: 10.1590/s0066-782x2003000400003
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, biochemical markers, and genetic polymorphisms in early coronary artery disease

Abstract: Of the classical risk factors, hypertension and diabetes mellitus were independently associated with early CAD. In addition to an unfavorable lipid profile, an increase in the thrombotic risk was identified in this population. An additive effect of the APO AI-CIII genes was observed in triglyceride levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…The data here are compatible to previously published reports as patients who develop with coronary artery disease when young are characterized by the presence of the aforementioned risk factors amongst others including obesity, systemic arterial hypertension, diabetes mellitus, unfavorable lipid profile, high levels of apolipoprotein B and low levels of apolipoprotein AI [8]. It is also important to stress that currently the majority of patients submitted to coronary artery bypass surgery are old, male, smokers and in bad physical conditions [9].…”
Section: Discussionsupporting
confidence: 91%
“…The data here are compatible to previously published reports as patients who develop with coronary artery disease when young are characterized by the presence of the aforementioned risk factors amongst others including obesity, systemic arterial hypertension, diabetes mellitus, unfavorable lipid profile, high levels of apolipoprotein B and low levels of apolipoprotein AI [8]. It is also important to stress that currently the majority of patients submitted to coronary artery bypass surgery are old, male, smokers and in bad physical conditions [9].…”
Section: Discussionsupporting
confidence: 91%
“…In cardiovascular diseases, blood concentrations of lipoproteins and lipids are influenced by hereditable risk factors and by environmental factors (Kannel et al 1961;Miller and Miller 1975). Several studies suggested that increased triglyceride levels and unfavourable lipid profile are independent risk factors for cardio-and cerebrovascular diseases (Meigs et al 2002;Izar et al 2003;Zhao et al 2010). In 2001, the National Cholesterol Education Program (NCEP) summarized other markers of coronary risk, classified as risk factors related to lifestyle (physical inactivity; obesity; and atherogenic diet) and emerging risk factors (lipoproteins; homocysteine; altered fasting glycaemia; and evidence of subclinical atherosclerosis) (2001).…”
Section: Introductionmentioning
confidence: 99%
“…The role of APOA5 alleles had already been widely studied (Szalai et al 2004;Vaessen et al 2006;Martinelli et al 2007;Maasz and Kisfali 2008a, b;Feitosa et al 2011), and a growing number of triglyceride modifying alleles are being identified (Ordovas et al 1991;Dallinga-Thie et al 1997; Baroni et al 2003;Talmud et al 2009). Some of them are associated with increased, while others with decreased triglyceride levels Baroni et al 2003;Izar et al 2003;Kathiresan and Melander 2008b;Kathiresan et al 2009); the analysis of their functional role in different diseases had already begun (Pedro-Botet et al 1992; Baroni et al 2003;Izar et al 2003;Frikke-Schmidt et al 2004;Ma et al 2004;Souverein et al 2005;Havasi et al 2006;Vaessen et al 2006;Freiberg et al 2008;Willer et al 2008;Kathiresan and Melander 2008a;Kathiresan et al 2009;Labreuche et al 2009;Perez-Martinez et al 2011). As increased levels of certain triglycerides can associate with the development of different vascular diseases, positive association between triglyceride level-elevating SNPs and polygenic vascular diseases has already been reported (Kannel et al 1961;Miller and Miller 1975;Salonen et al 1982;Ordovas et al 1991;Pedro-Botet et al 1992;Meigs et al 2002;Baroni et al 2003;Izar et al 2003;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, other triglyceride modifying polymorphisms came into focus, which may also have role in development of different diseases [2,12,15,16,19,[23][24][25]. Some variants of these are mentioned in connection with increased, while others with decreased triglyceride levels [16,23,24,26,27]. The elevated levels of certain triglycerides may have a higher risk for several vascular diseases, moreover significant associations between triglyceride level-elevating and polymorphisms were confirmed [1, 2, 4, 5, 12-15, 17, 28, 26, 29-32, 25].…”
mentioning
confidence: 99%